The Application of Facial Expression Recognition in Reducing Inaccuracy in Pain Scale Intensity Identification - Mohd Ariff bin Sulaiman; Nur Azaliah Abu Bakar; Suraya Yaacob; Farashazillah Yahya (Penerbit UTM Press, 2021)
The correct assessment is essential to ensure the proper treatment for the patient and pain is relieved. Thus, the inaccuracy in identifying the pain scale intensity has to be at the lowest point. However, many studies point out that the existing pain scale intensity identification is mainly based on human perception and individual pain endurance threshold. Therefore, the results can be varied and also being manipulated by the patients. This article aims to propose a Machine Learning technique to recognize and analyse facial expression recognition during pain assessment. The paper describes the relationship of the problem, solution and the impact of the solution. It further explains how the application of machine learning in pain detection can be applied starting from features selection an Data sets collection, followed by analyzing and concludes by discussing the idea of improvements of the solution.